Cônicas: Situações Didáticas para o ensino médio - Bonfim, Rosana Silva [UNESP] (2015)
The conics form a topic of great relevance in the modern technological development; however, their study in high school, most of the time, is made from a purely analytical, decontextualized and fragmented approach. The Curriculum of Mathematics, Department of São Paulo State Education (SEE) includes the conics from the perspective of analytic geometry and with little reference to its use in our daily lives. The teaching of conics is, when it happens, for the most students, of shallow and restricted form a short period of time, which causes some contempt by the students and even some teachers who, for lack of proper training, unaware of its importance and usefulness. Our goal is to present alternatives differentiated for teaching of Conics, based on the Theory of Didactic Situations developed by Guy Brousseau, which indicates the creation of didactic situations that favor the investigation of the student and approaching the way the scientific activity is produced. We present some didactic situations that can be developed in the third year of high school and seeking a do math closer to the real life of the student, allowing the exploration and the research through the of folding paper and GeoGebra software